DETERMINANTS OF SERVICE LOGISTIC INNOVATION AND ITS CAPABILITY IN CAMBODIA USING THE STRUCTURAL EQUATION MODEL - Sin, Chanthy; Phon, Sophat; Touch, Visalsok (jfpublisher, 2024)
Logistics and transportation are becoming increasingly significant in international trade relations as a means of promoting growth by enabling the export and import of goods in developing and developed countries. Hence, this study employs a logistic case study of Cambodia, providing detailed information about logistics performance, services, and capacity. Additionally, this study utilizes the strategy-structure-performance framework to investigate factors influencing a firm’s logistics service innovation capabilities and customer satisfaction, as well as the firm’s resource-based outlook through structural Equation Model (SEM) analysis. From December 2022 to February 2023, a self-administered survey with a structured questionnaire was used to collect data from 396 wholesalers in SMEs with relevant experience in using logistic services in Cambodia to examine the hypothesized relationships. According to the findings, key factors of demanded-oriented service, process capability, information process, and logistic service quality positively impacted to a firm’s logistic service and its innovation capability and customer satisfaction (Coef=0.96), while the other three research variables, customer orientation, physical supply flexibility, demand management flexibility, logistic service quality, and process competence, have a significant impact on logistic service innovation. This means that logistic services and innovation are very vital to satisfy the customers and growth in Cambodia.